Study of hydrogen risk in a marine nuclear reactor during a loss of coolant accident - Vilela, Guilherme Trindade (2023)
Marine nuclear reactors, especially when powering submarines, take most of the benefits which this technology can provide. Due to their high power density, small fuel storage volume required, and the long or even dismissed interval of refueling, marine reactors provide good applicability of nuclear technology. However, the cladding of the reactor fuel elements employs materials that can generate hydrogen posing combustion risks and threats to the containment integrity. Space is limited in a marine reactor containment, and a small amount of hydrogen released can become a potential combustion source. In this study, a computational simulation using the commercial multi-purpose code ANSYS Fluent was performed to provide local distributions of temperature, pressure, hydrogen, and steam concentrations in a reactor containment. These parameters were used for the assessment of hydrogen combustion risk during an accidental scenario. The utilization of a multipurpose code presented the inconvenience of the absence of in-built phase change models for condensation modeling. The condensation phenomenon was modeled in the code through the implementation of external subroutines to introduce steam mass sinks and water mass sources on the domain cells. The magnitude of these sources was calculated based on empirical condensation correlations. During the progression of an accident, condensation plays an important role in limiting pressure increase and increasing heat removal in the containment structures. Moreover, condensation also affects the hydrogen combustion risk as it reduces the volume fraction of steam in the containment atmosphere and allows the expansion of the flammable hydrogen cloud. Hydrogen combustion risk and the possibility of slow deflagration, flame acceleration, and deflagration to detonation transition were assessed from the utilization of the Sigma and Lambda criteria. A theoretical zero-dimensional model has been proposed for the validation of the simulation results, due to the absence of experimental data.